THE DYNAMICS OF SPIRITUALITY IN THE OLD AGE: THE PERSPECTIVE OF MAQASHID AL-SHARIAH AND PSYCHOLOGY - Mubasirun, Mubasirun; Sa'adi, Sa'adi (AKADEMIKA: Jurnal Pemikiran Islam, 2021)
This study aimed to describe the dynamics of spirituality among the retirement community viewed from the perspective of Maqashid al-Shari’ah and Psychology that are the factors that cause the strengthening of the activities of the spirituality to liberate itself from the situation of post-power syndrome. In-depth interviews and observations, data reduction, data presentation, and verification are the mainstay methods in the data collection and analysis of this study. The results of this study show that the mashlahah (benefit) that is the meeting point between the theory of Maqashid al-Shari’ah and Psychology become a basic need for the retirement community. In their old age, the retirement community precisely strengthens their spirituality. The strengthening factors of their spirituality are the motivation of the fulfillment of the needs of the world and hereafter, free of social conflicts, as well as the awards and respect from their surrounding community because of their devotion and example (social devotion and leadership).